Not All Lesioned Tissue Is Equal: Identifying Pericavitational Areas in Chronic Stroke With Tissue Integrity Gradation via T2w T1w Ratio - Krishnamurthy, Lisa C.; Krishnamurthy, Venkatagiri; Rodriguez, Amy D.; McGregor, Keith M.; Glassman, Clara N.; Champion, Gabriell S.; Rocha, Natalie; Harnish, Stacy M.; Belagaje, Samir R.; Kundu, Suprateek; Crosson, Bruce A. (Frontiers in Neuroscience, 2021)
Stroke-related tissue damage within lesioned brain areas is topologically non-uniform and has underlying tissue composition changes that may have important implications for rehabilitation. However, we know of no uniformly accepted, objective non-invasive methodology to identify pericavitational areas within the chronic stroke lesion. To fill this gap, we propose a novel Magnetic Resonance Imaging (MRI) methodology to objectively quantify the lesion core and surrounding pericavitational perimeter, which we call Tissue Integrity Gradation via T2w T1w Ratio (TIGR). TIGR uses standard T1-weighted (T1w) and T2-weighted (T2w) anatomical images routinely collected in the clinical setting. TIGR maps are analyzed with relation to subject-specific grey matter and cerebrospinal fluid thresholds and binned to create a false colormap of tissue damage within the stroke lesion and further categorized into low, medium, and high damage areas. We validate TIGR by showing that cerebral blood flow within the lesion reduces with greater tissue damage (p=0.005). We further show that significant task activity can be detected in pericavitational areas and that medium damage areas contain a significantly lower magnitude of hemodynamic response function than adjacent damage areas (p<0.0001). We also demonstrate the feasibility of using TIGR maps to extract multivariate brain-behavior relationships (p<0.05) and show general agreement in location compared to binary lesion, T1w-only, and T2w-only maps, but that the extent of brain behavior maps may depend on signal sensitivity as denoted by the sparseness coefficient (p<0.0001). Finally, we show the feasibility of quantifying TIGR in early and late subacute stroke phases, where higher damage areas were smaller in size (p=0.002) and that lesioned voxels transition from lower to higher damage with increasing time post-stroke (p=0.004). We conclude that TIGR is able to: 1) identify tissue damage gradient within the stroke lesion across different post-stroke timepoints, and 2) more objectively delineate lesion core from pericavitational areas wherein such areas demonstrate reasonable and expected physiological and functional impairments. Importantly, because T1w and T2w scans are routinely collected in the clinic, TIGR maps can readily be incorporated in clinical settings without additional imaging costs or patient burden to facilitate decision processes related to rehabilitation planning.